1993
DOI: 10.1111/j.1476-5381.1993.tb12819.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 does not mediate hypoxic vasoconstriction in canine isolated blood vessels: effect of BQ‐123

Abstract: 1 The role of endothelin-1 in mediating the phenomenon of hypoxic vasoconstriction was examined in canine, isolated pulmonary, circumflex coronary and femoral arterial rings. 2 In tissues with an intact endothelium, the exogenous application of endothelin-1 (0.1-300nM) caused concentration-dependent increases in canine, isolated pulmonary artery tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
3

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 18 publications
(22 reference statements)
1
18
3
Order By: Relevance
“…Furthermore, our preparations did not need priming with a constrictor agent to react to hypoxia. Both findings are at variance with previous reports, according to which integrity of the endothelium and some basal tone are a prerequisite for the hypoxic response (Holden & McCall, 1984;Johns et al 1989;Rodman et al 1990;Demiryurek et al 1991Demiryurek et al , 1993Omar & Wolin 1992;Douglas et al 1993;Ogawa et al 1993). A developmental factor, relating to the age of our preparation, is unlikely to account for the difference.…”
Section: -10contrasting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, our preparations did not need priming with a constrictor agent to react to hypoxia. Both findings are at variance with previous reports, according to which integrity of the endothelium and some basal tone are a prerequisite for the hypoxic response (Holden & McCall, 1984;Johns et al 1989;Rodman et al 1990;Demiryurek et al 1991Demiryurek et al , 1993Omar & Wolin 1992;Douglas et al 1993;Ogawa et al 1993). A developmental factor, relating to the age of our preparation, is unlikely to account for the difference.…”
Section: -10contrasting
confidence: 56%
“…A developmental factor, relating to the age of our preparation, is unlikely to account for the difference. More plausibly, the explanation is linked to the source of the preparation since earlier results apply primarily to conductance and not to resistance vessels (Holden & McCall, 1984;Johns et al 1989;Rodman et al 1990;Demiryurek et al 1991Demiryurek et al , 1993Douglas et al 1993;Ogawa et al 1993). Hence one may surmise the existence of two kinds of vessels in the pulmonary vascular bed, having in common the susceptibility to hypoxia but differing for the conditions under which this quality is expressed.…”
Section: -10mentioning
confidence: 97%
“…Indirect support for this conclusion comes from the ®nding that pulmonary hypoxia raises plasma ET-1 levels by increasing the expression of ET-1 mRNA, and increases the release of ET-1 from pulmonary artery endothelial cells (Giaid et al, 1993;Elton et al, 1992;Li et al, 1994a;. However, it should be noted that the suggestion that ET-1 acts as a mediator of HPV remains controversial and a number of authors have shown that ET receptor antagonists are unable to inhibit HPV and it has been proposed that an unidenti®ed vasoconstrictor distinct from ET-1 may act as the primary mediator of HPV (Wadsworth, 1994;Douglas et al, 1993;Gaine et al, 1998;. Thus, it may be more likely that ET-1 contributes to the development of chronic hypoxic pulmonary hypertension rather than to the acute response to hypoxia (Chen et al, 1997;Bonvallet et al, 1994;Prie et al, 1997;Barton et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that big endothelin-1 alone markedly increased systemic vascular resistance but had no effect on hyperoxic or hypoxic pulmonary vascular resistance. Other authors have also been unable to inhibit HPV with endothelin receptor antagonists, including bosentan [15,[21][22][23]. Variable results of effects of endothelin receptor blockers on HPV in different experimental models may be explained by variable antagonism of tonic effects of endothelins by circulating or endothelium-derived vasodilating mediators.…”
Section: Hypoxic Pulmonary Vasoconstrictionmentioning
confidence: 99%
“…Hypoxia has been reported to increase the level of immunoreactive endothelin-1 in the plasma and of endothelin-1 messenger ribonucleic acid in the lung and right atrium [12,20]. However, selective as well as nonselective endothelin receptor blockers have been shown to inhibit HPV in some studies [8][9][10][11][12][13][14] but not in others [15,[21][22][23]. These discrepancies might be explained, at least in part, by variable release of endogenous NO, which has been shown to limit HPV in intact animals [24,25].…”
mentioning
confidence: 99%